Low impact of regular PCR testing on presence at work site during the COVID-19 pandemic: experiences during an open observational study in Lower Saxony 2020-21 - Lisa K. Seiler; Susanne Stolpe; Nils Stanislawski; Frank Stahl; Martin Witt; Rebecca Jonczyk; Stefanie Heiden; Holger Blume; Bernd Kowall; Cornelia Blume (BMC, 2023)
Abstract Background Since social distancing during the COVID-19-pandemic had a profound impact on professional life, this study investigated the effect of PCR testing on on-site work. Methods PCR screening, antibody testing, and questionnaires offered to 4,890 working adults in Lower Saxony were accompanied by data collection on demographics, family status, comorbidities, social situation, health-related behavior, and the number of work-related contacts. Relative risks (RR) with 95 % confidence intervals were estimated for the associations between regular PCR testing and other work and health-related variables, respectively, and working on-site. Analyses were stratified by the suitability of work tasks for mobile office. Results Between April 2020 and February 2021, 1,643 employees underwent PCR testing. Whether mobile working was possible strongly influenced the work behavior. Persons whose work was suitable for mobile office (mobile workers) had a lower probability of working on-site than persons whose work was not suitable for mobile office (RR = 0.09 (95 % CI: 0.07 - 0.12)). In mobile workers, regular PCR-testing was slightly associated with working on-site (RR = 1.19 (0.66; 2.14)). In those whose working place was unsuitable for mobile office, the corresponding RR was 0.94 (0.80; 1.09). Compared to persons without chronic diseases, chronically ill persons worked less often on-site if their workplace was suitable for mobile office (RR = 0.73 (0.40; 1.33)), but even more often if their workplace was not suitable for mobile office (RR = 1.17 (1.04; 1.33)). Conclusion If work was suitable for mobile office, regular PCR-testing did not have a strong effect on presence at the work site. Trial registration An ethics vote of the responsible medical association (Lower Saxony, Germany) retrospectively approved the evaluation of the collected subject data in a pseudonymized form in the context of medical studies (No. Bo/30/2020; Bo/31/2020; Bo/32/2020).